2014
DOI: 10.2478/agri-2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Chlorophyll Meter Measurement in Winter Wheat at Field Scale Level

Abstract: This paper examines the relationship among chlorophyll meter Yara N-Tester readings, nutrition status and growth parameters (leaf area index (LAI), plant height) of the winter wheat plants. Data used in this study were collected in 2010 from two fields located in the Czech Republic (area 52 and 38 ha) from different farms, both with uniform and conventional crop management. The monitoring of crop stands was done at growth stage BBCH 30 in a regular sampling grid with 150 m distance between points (27 and 18 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In this study the pigments content affect by foliar treatments. However, in this regards Lukas et al (2014) reported that the relationships between crop parameters and chlorophyll meter readings are not generalisable and thus the interpretation of N-Tester results has to be done separately for each field. Numerous roles have been proposed for anthocyanins induced during abiotic stresses including functioning as reactive oxygen species (ROS) scavengers, photoprotectants, and stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In this study the pigments content affect by foliar treatments. However, in this regards Lukas et al (2014) reported that the relationships between crop parameters and chlorophyll meter readings are not generalisable and thus the interpretation of N-Tester results has to be done separately for each field. Numerous roles have been proposed for anthocyanins induced during abiotic stresses including functioning as reactive oxygen species (ROS) scavengers, photoprotectants, and stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll content was closely related to crop health, photosynthetic capacity and crop yield ( Lukas et al, 2014 ). C 3 plants are more sensitive to elevated CO 2 than C 4 plants ( Leakey et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%